Dysfunctional uterine bleeding in premenopausal. - Soihet, Samoel (2015)
Any woman who fluctuates between 35 and 45 years in which the rate and amount of menstrual flow is altered, it must be tested with a diagnosis of certainty it is not caused by a benign or malignant neoplasia, to be classified as a case of hemorrhage dysfunctional uterine: HUD premenopausal. A woman is in the menopausal stage, when being in that age does not rule over 6-12 consecutive months without pregnancy or other pathological cause.